Legal Consequences Of Default On The Sale And Purchase Of Land In Indonesia In Case Number 42/PDT.G/2018/PN GSK - Nobella indradjaja; Chamdani Chamdani (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The occurrence of default in an agreement as a source of sale and purchase and a sale and purchase agreement that always begins with a contractual relationship (the characteristic of default is always preceded by a contractual relationship) can be caused by several elements, one of which is one of the elements.Articles 1321 and 1449 of the Penal Code provide the legal basis for land sale and purchase agreements by mistake. According to the Penal Code Article 1321: According to Article 1449 of the Penal Code" If obtained by coercion, fraud, or error, there is no valid agreement." A claim to cancel a contract can be made if the contract was made under coercion, toan oversight, or through fraud